Chromosome mapping of Rett syndrome: a likely candidate region on the telomere of Xq. Issue 4 (April 1998) - Xiang, F; Zhang, Z; Clarke, A; Joseluiz, P; Sakkubai, N; Sarojini, B; Delozier-Blanchet, C D; Hansmann, I; Edström, L; Anvret, M
Abstract : Rett syndrome (RS) is a disease of neurological development. First reported 30 years ago in 1966, its biological and genetic basis remains obscure. RS is commonly thought of as an X linked dominant disorder lethal to hemizygous males. The few familial cases would arise through mosaicism or because of occasional females failing to manifest the disorder through skewed X inactivation in relevant cell types. We have one family where the mother and daughter are affected with RS, and which can be explained according to this hypothesis. If the alternative proposal of Thomas (1996) is correct, that the lack of males affected by such disorders is the result of a high male to female ratio of germline mutations rather than of gestational lethality, then the RS gene should be located on the grandpaternal chromosome. Genomic screening with markers covering the whole X chromosome has been performed. Studies using multiple informative markers indicate that the RS locus is likely to be located close to one of the X chromosome telomeres. Further investigations in eight additional families suggest the most likely region for the RS gene to be is the distal part of Xq (Xq28).